KEPATUHAN PARA PIHAK DALAM MENYELESAIKAN SENGKETA MELALUI ARBITRASE SESUAI DENGAN ISI PERJANJIAN (STUDI PERDATA PERJANJIAN JEMBATAN SELAT RENGIT DI KABUPATEN KEPULAUAN MERANTI) - Firmansyah Firmansyah; Firdaus Firdaus; Setia Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In a construction cooperation there are two parties who are mutually boundby the agreement. The agreement made by both parties is used as the basis andlegal umbrella in construction work. It contains rights and obligations,implementation procedures and settlement efforts if there is a dispute between thetwo parties. The parties to an agreement are usually based on a specific purposeor purpose. The agreement has the goal of creating better conditions for bothparties. However, an agreement can also be violated to the detriment of the otherparty or the term is default. Therefore, this study aims, First, to explain thereasons related to the occurrence of defaults, especially regarding efforts toresolve them. Second, to determine the level of compliance of the partiesregarding efforts to settle defaults in accordance with the contents of theagreement.This type of research can be classified in the type of normative research.This research was conducted to determine the level of compliance of the parties,especially related to the contents of the agreement. This agreement forms thebasis for implementing the Rengit Strait Bridge Construction project in MerantiIslands Regency, Riau Province.From the results of the research problem there are two main things thatcan be concluded. First, the plaintiff's reasons, in this case the Meranti IslandsDistrict Government, filed a civil lawsuit for default to the District Court.Whereas in the contract clause it is explained regarding efforts to resolve disputesthrough arbitration. Second, the compliance of the parties in resolving disputesthat are not in accordance with the contents of the agreement that has been madebefore. The author's suggestions, first, to make efforts to resolve if a disputeoccurs such as default should be made based on the contents of the agreement.Second, to comply with each of the contents of the agreement must be based onthe self of each party, considering that the agreement is law for both parties,especially when it comes to efforts to resolve disputes arising from the agreement.